(untitled) (Orfeu, 2025)
“Stray-Dog body-identities” consists of artistic research which explores the interface between music and movement through popular song and choreographic composition with the aim of producing live performance and audiovisual content. This investigation takes place in the collaborative practice between two researchers, a performer and composer of popular song and a contemporary dance choreography composer. The interaction between these languages ​​reveals strategies, operations and elements of the creative processes not perceived by itselves in isolation. Thus, the artists observe their own processes and perceive the oral and corporal knowledge inscribed in their practices. In addition to the reflection on the processes themselves, there is intentionality and search for countercolonial and antifascist poetics that allow to rethink practices in the university promoting the expansion of fields of knowledge at a glocal level.